2007
DOI: 10.1111/j.1442-2042.2007.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Voiding patterns in men and women with lower urinary tract symptoms combined with nocturia

Abstract: Aim: We evaluated differences between men and women with lower urinary tract symptoms (LUTS) combined with nocturia. Methods: A total of 71 age-matched female-male pairs (median 58, range 20-81 years) who had moderate to severe LUTS and nocturia of more than once per night were enrolled in this study. Results: In the younger group (<50 years), the International Prostate Symptom Score (I-PSS) results of the sexes were not significantly different. However, although total I-PSS results in the elderly group (Ն50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…A limitation we recognize is that sex ratio is different between the younger and older age group, although we doubt that this would have influenced our conclusions. Paick et al observed a higher NVV too in older men in a study on 71 age‐matched female–male pairs. In this study, women had a significantly lower bladder capacity, which is also confirmed by our results .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A limitation we recognize is that sex ratio is different between the younger and older age group, although we doubt that this would have influenced our conclusions. Paick et al observed a higher NVV too in older men in a study on 71 age‐matched female–male pairs. In this study, women had a significantly lower bladder capacity, which is also confirmed by our results .…”
Section: Discussionmentioning
confidence: 93%
“…In this study, women had a significantly lower bladder capacity, which is also confirmed by our results. 21 Weiss et al 19 found a predominance of reduced nocturnal bladder capacity in younger patients and a predominance of NP in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some conditions and diseases leading to nocturia may involve one or more of these factors to cause nocturia. Interestingly, the relative roles of these factors may differ between genders as it has been reported that male nocturia more often is related to nocturnal polyuria, whereas female nocturia more often is related to a small bladder capacity 28 . The relative roles of the various factors may also differ between ethnic groups 29 …”
Section: Pathophysiology Of Nocturiamentioning
confidence: 99%